Progress in metal-free cooperative catalysis for the ring-opening copolymerization of cyclic anhydrides and epoxides. (December 2019) - Pappuru, Sreenath; Chakraborty, Debashis
Graphical abstract: Ring-opening alternating copolymerization (ROAP) of epoxides with cyclic anhydrides is an important polymerization reaction to illustrate significant features of metal-free cooperative catalysts. Highlights: Recent advancements in metal-free cooperative catalysis towards ring-opening copolymerization of cyclic anhydrides and epoxides was described. Simplicity of metal-free catalysts and their catalytic efficiency towards polymers molar mass control and stereo-/regioselectivity control was explained. Cooperativity between the acidic and basic catalytic sites of readily available LAs and LBs, for enhancing the polymerization activity was described. Abstract: Recent progress in the design of metal-free Lewis pair catalysts indicates a bright future for the synthesis of various polyesters with broad applications. In the present review, we attempt to highlight the recent advancements and opportunities in the use of metal-free cooperative catalysts or initiators for polymerization reactions. The ring-opening alternating copolymerization (ROAP) of epoxides with cyclic anhydrides is a typical typical polymerization reaction used here to illustrate some of the features of metal-free cooperative catalysts. In addition to the simple simplicity in the structural features of the catalysts and the desirable metal-free polyesters/polycarbonate products, these metal-free catalysts also exhibit impressive catalytic efficiency, molar mass control, and stereo-/regioselectivity. We believe that metal-free cooperative catalysis will continue to drive innovation into polymer chemistry research in the near future.